Trusting technology: Women aged 40-49 years participating in screening for breast cancer-an exploratory study - Karen Willis; Janeen Baxter (Elsevier, 2003)
Abstract Objective:This paper reports key findings from an exploratory study of factors associated with women's decision to participate in mass mammography screening in Tasmania. In particular, we explored factors that contribute to the choice to participate in screening by women who are outside the primary target group, and for whom the evidence of benefit remains contentious. Methods:Semi‐structured interviews were conducted with a small sample of women aged between 40 and 49 years in rural Tasmania who had participated in mammography screening. Results:Key ideas that appeared to shape participation included the fear of breast cancer, trust in technology, and taking responsibility for health. Information provision is also an important factor in shaping participation patterns. Conclusions and implications:In order to facilitate informed consent, information provision in this area should take account of the dominant ideas that shape the decision to participate in breast cancer screening.